2021
DOI: 10.3390/reports4010007
|View full text |Cite
|
Sign up to set email alerts
|

AHR:IKAROS Interaction Promotes Platelet Biogenesis in Response to SR1

Abstract: In vitro, the differentiation of megakaryocytes (MKs) is improved by aryl-hydrocarbon receptor (AHR) antagonists such as StemRegenin 1 (SR1), an effect physiologically recapitulated by the presence of stromal mesenchymal cells (MSC). This inhibition promotes the amplification of a CD34+CD41low population able to mature as MKs with a high capacity for platelet production. In this short report, we showed that the emergence of the thrombocytogenic precursors and the enhancement of platelet production triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Improving the efficiency of MkP or MK precursor generation from HSPCs is a critical step in inducing functional MK and platelet production in vitro. Previous studies indicated that an MK precursor population with strong MK differentiation potential can be enriched by subculturing the cells with bone marrow mesenchymal stromal cells or StemRegenin 1 treatment [ 37 , 38 ]. It remains challenging to increase the committed differentiation of MkPs from HSPCs using new inducing agents.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the efficiency of MkP or MK precursor generation from HSPCs is a critical step in inducing functional MK and platelet production in vitro. Previous studies indicated that an MK precursor population with strong MK differentiation potential can be enriched by subculturing the cells with bone marrow mesenchymal stromal cells or StemRegenin 1 treatment [ 37 , 38 ]. It remains challenging to increase the committed differentiation of MkPs from HSPCs using new inducing agents.…”
Section: Discussionmentioning
confidence: 99%